Effectiveness of Testicular Workup for Ischemia and Suspected Torsion Score in Diagnosis of Testicular Torsion in Children - Hai, A H M Abdul; Yeasmin, Laila; Hasan, Gazi Mahmud Ul; Abir, Ashekin; Mohanta, Pankaj; Shakib, S M Nazmus; Mahamud, Md. Tazmir; Hasan, Nayeem; Huq, Ashraf Ul (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Testicular torsion is a surgical emergency mandating immediate intervention and is commonly seen in children presenting with acute scrotum. The likelihood of testicular salvage increases with early diagnosis and explora tion. Color doppler is frequently recommended for diagnosis. Enhancing the probabilities of testicular viability can be achieved by minimizing the waiting time by the implementation of a judicial doppler requisition before proceeding with explora tion. The testicular workup for ischemia and suspected torsion (TWIST) score has been developed and validated specifically for the assessment of this condition in the pediatric population. Objective: To diagnose testicular torsion using TWIST score. Methods: This study included a cohort of 108 pediatric patients with acute scrotum between September 2022 to August 2025. Everyone who participated underwent assessment and were classified into low-risk (1-2 points), intermediate-risk (3-4 points), or high-risk (5-7 points) categories based on their TWIST score. Color dopplerof testes were conducted in each case and data was documented. Statistical analysis was performed by SPSS version 27. Results: Forty-two, (38.88%), 12 (11.11%), and 54 boys (50%) were categorized into low, intermediate, and high-risk categories respectively, based on the score they received. No torsion cases were present in the low-risk group. Two patients of intermediate risk group were diagnosed as torsion where 50 patients of the 54 high-risk children were diagnosed with torsion, and 1 had epididymo-orchitis and the other 3 were torsion of testicular appendages confirmed by doppler. The sensitivity, specificity, positive predictive value and negative predictive value of this study were 100%, 91.30%, 92.59 % and 100% respectively. Conclusion: The TWIST score is a highly effective clinical tool utilized for the diagnosis of testicular torsion in pediatric patients. The utilization of this technique has the potential to decrease the incidence of acute scrotum-related morbidity, particularly in cases of torsion, by prompt detection and the prevention of unnecessary delays in performing doppler imaging. Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 15-20